Neck and décolleté regeneration in women over 45: combined biostimulation protocol - Guariglia, Michele (Aesthetic Medicine, 2025)
Objectives: Patients over 45 years of age experience aesthetic medicine dynamically. Neck and décolleté represent an area affected by aging: roughness, laxity, redness and blemishes can cause social distress in patients who do not typically cover their neck. Due to the reduction of collagen and elastin, folds and wrinkles are formed with less elastic and toned skin. This is made more noticeable by the effect the sun’s UV rays have on unprotected skin. The aim of the study is to evaluate a new neck and décolleté biostimulation protocol with hyaluronic acid, glycerol, and calcium hydroxyapatite. Materials and methods: 12 patients between 45 and 65 years old were subjected to neck and décolleté treatment with Hyaluronic Acid fillers (20 + 17.5 mg/ml) (Belotero® Revive), for 3 sessions each spaced 20 days apart. One month after the final session, a 1.5 cc injection of calcium hydroxylapatite filler (Radiesse®), diluted at a ratio of 1:3, was administered. Patients were asked if they felt uncomfortable exposing their neckline. Results: Belotero® Revive improves hydration thanks to the combination of hyaluronic acid and glycerol which has hygroscopic properties. It promotes the absorption of water from the dermis to the stratum corneum; glycerol acts as a protective shield for hyaluronic acid, slowing down its degradation and prolonging its effect. Décolleté wrinkles can be effectively treated with calcium hydroxyapatite which provides an immediate filling effect, therefore reducing their prominence. The calcium hydroxylapatite microspheres contained in the filler stimulate the production of new collagen in the treated area over time. This process helps improve skin quality by promoting regeneration, increasing firmness and elasticity, and evening out skin tone, thereby counteracting the effects of aging and oxidative damage caused by sun exposure. After five months, 75% of the women reported feeling no discomfort when exposing their décolleté, compared to only 20% at the beginning of the treatment. Conclusions: The combined biostimulation protocol made it possible to obtain important results on the neck and décolleté, redefining the texture, improving brightness, hydration and tone, with extreme relaxation of fine wrinkles and reduction of redness and blemishes. Women over the age of 45 with visible signs of skin aging on the neck and décolleté can achieve significant improvements in this area. As a result, many feel more comfortable wearing necklines they had previously avoided, leading to a sense of rejuvenation, increased self-confidence, and greater self-awareness. The protocol significantly delays the skin aging process.